Hubungan Pengetahuan Ibu Hamil Tentang Anemia dengan Kepatuhan Konsumsi Tablet Fe di BPM Boloni Tanaka Kec. Medan Johor Tahun 2023 - Anggriani Silitonga; Khairunnisa Situmorang; Ester Simanullang; Anna Waris Nainggolan (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2024)
Insufficient knowledge about anemia has an influence on health behavior, especially when a woman is pregnant, which will result in less than optimal health behavior for pregnant women to prevent pregnancy anemia. Pregnant women who have less knowledge about anemia can result in less consumption of foods containing iron during pregnancy due to their ignorance. Objective: To determine the relationship between pregnant women's knowledge about anemia and compliance with taking Fe tablets. Research population: the population used is the population of all patients at BPM Boloni Tanaka Kec. Medan Johor in 2023 as many as 32 pregnant women. Research Type: The type of research used is an analytical survey with a cross sectional research design. Data collection uses a questionnaire. Data were processed using univariate analysis using descriptive statistics and bivariate analysis using the Chi-square test. The results of the Chi-square test analysis show that the p value = 0.000, which means less than α = 0.05, so it can be concluded that there is a significant relationship between pregnant women's knowledge about anemia and compliance with consuming Fe tablets at BPM Boloni Tanaka District. Medan Johor in 2023.